Detailed Study on the Effect of Oxidant, Dopant and MO Additive Loading on Morphology, Conductivity and Dielectric Constant of 3D Conducting Polymer PPy/\(\alpha\)-Fe2O3 Nanocomposites - Mahatme, U. B.; Gedam, R. S.; Tidke, G. D.; Utane, R. D.; Rangari, A. H. (Advanced Aspects of Engineering Research Vol. 6, 2021)
Conducting polymer (CP) polypyrrole (PPy) and their nanocomposites (NCs) with metal oxide \(\alpha\)-Fe2O3 (CP/MO) are synthesized by in situ chemical oxidation polymerization using various oxidants and dopants by keeping different molar percentage of MO with monomers. The prepared CPs and their CP/MO NCs PPy/\(\alpha\)-Fe2O3 are characterized by FTIR. Their morphology has studied by SEM and TEM techniques. Presence of identity bonds on the FTIR spectrograms ensures the formation of CPs and their NCs. SEM images show the presence of nearly spherical nanoparticles (NPs) on surface of CP and its composites. TEM images show the presence of NPs embed polymer net having thickness below 20 nm in PPy and, nanocluster/nanorods/nanosheets embed polymer chain of spherical NPs in composites, PPy/\(\alpha\)-Fe2O3. The room temperature ac conductivity (\(\sigma\)ac) and dielectric constant (\(\epsilon\)’) against frequency in the range 1 Hz to 40 MHz has measured using computer control impedance analyzer. The increment in ac conductivity (\(\sigma\)ac) of CP and all its composites with rise in frequency assigned the quantum mechanical tunneling (QMT) in all materials under the present study and shows their polycrystalline disorder (amorphous and crystalline) structure. The IR bands, structure, morphology, \(\sigma\)ac and \(\epsilon\)’ shows dependence on type of oxidant, dopant and wt% of added MO. Oxidants and dopants show the remarkable and intense effect on the frequency response of ac conductivity and dielectric constant of the composites.